Optimum sizing of steam turbines for concentrated solar power plants - Poullikkas, Andreas (2012)
In this work, a selection of the optimum steam turbine type and size for integration in concentrated solar power (CSP) plants is carried out. In particular, the optimum steam turbine input and output interfaces for a range of CSP plant capacity sizes are identified. Also, efficiency and electricity unit cost curves for various steam turbine capacities are estimated by using a combination of the Steam Pro software module of the Thermoflow Suite 18 package and the IPP v2.1 optimization software tool. The results indicate that the estimated efficiency and the expected specific capital cost of the power block are very important criteria in choosing the best steam turbine size of a CSP plant. For capacity sizes of 10kWe up to 50MWe, the steam turbine efficiency increases and the steam turbine expected specific capital cost of the power block decreases at a high rate, whereas for larger sizes they remain almost constant. Thus, there is significant efficiency gains to be realized and large cost savings in increasing the turbine size up to 50MWe. Finally, although the cost of electricity of a CSP plant with capacities greater than 1MWe is significantly reduced to less than 1US$/kWh, currently such technology can only become economically viable through supporting schemes.